Titanic - Cameron, James; Paxton, Bill, 1955-; Billy Zane; Frances Fisher; Gloria Stuart; Kate Winslet; Kathy Bates; Leonardo DiCaprio (USA Paramount, 1997)
Its name stirs the imagination... Titanic. The unsinkable ship. The unimaginable catastrophe. The untold stories that lay in mystery two and a half miles beneath the waves of the North Atlantic. What buried tale of love, bravery, treasure and treachery, hidden by time and tragedy, waits here to be discovered? A beautiful socialite. A penniless artist. A priceless diamond. A romance so passionate that nothing on earth could stop it. A destiny so incredible that no one could have imagined it. A collision of lives that could only have happened on Titanic, the ship of dreams. The secrets are about to unfold...
Fictional romantic tale of a rich girl and poor boy who meet on the ill-fated voyage of the 'unsinkable' ship.
James Cameron
Languages : English, Polish Subtitles : English, Turkish, Estonian, Latvian, Lettish, Lithuanian
1997 Oscar Academy Award Best Picture
Keywords: Drama; Romance; Action -- Oscar Academy Award